Spatiotemporal analysis of phenological metrics on the Qinghai-Tibet Plateau based on multiple vegetation indices - Chen, Tao; Chen, Zhu; Xie, Guojing (Frontiers in Environmental Science, 2024)
As global climate change intensifies, understanding the response mechanisms and adaptive capacities of ecosystems to climate change has become a core focus in environmental science. The Qinghai-Tibet Plateau (QTP), a region highly sensitive to global climate change, shows vegetation phenological shifts that reflect the ecosystem’s response to climate fluctuations. However, how phenological metrics extracted from different vegetation indices affect our understanding of these shifts in the region remains unclear. This study analyzes the start (SOS) and end (EOS) of the growing season on the QTP from 1982 to 2015 using GIMMS NDVI3g data. These metrics were compared with phenological data derived from GIMMS LAI3g and MODIS EVI2 data. The results indicate that phenological metrics derived from different vegetation indices (NDVI, LAI, and EVI2) are generally consistent in their spatiotemporal distribution and show significant correlations. However, regional differences and temporal inconsistencies were observed. This comparative analysis reveals the strengths and limitations of various vegetation indices in phenological metric extraction. The results offer crucial insights for enhancing the precision of phenological modeling and highlight the significance of choosing suitable vegetation indices in future studies on phenology.